2021
DOI: 10.2113/2021/9171191
|View full text |Cite
|
Sign up to set email alerts
|

Heat Flow Correction for the High-Permeability Formation: A Case Study for Xiong’an New Area

Abstract: The Xiong’an New Area is located at the western Bohai Bay Basin, 150 km south of Beijing, China. The area has tremendous high heat flow value within the sedimentary layer, and the average value can reach 90 mW·m-2 within the Niutuozhen Uplift. However, combining the basal heat flow at the top of the metamorphic layer with the heat flow value which was contributed by the radiogenic heat production from the overlying formation, the surface heat flow value was only 65.1 mW·m-2 in this area. Thus, the heat flow va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The thermal contours were less close to vertical in low hydraulic conductivity layers compared to those with high hydraulic conductivity. Moreover, [64][65][66] also associated the bending of the thermal contours with the refraction of the heat flow. They demonstrated that the variation of thermal conductivity within the aquifer materials produced the refraction.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal contours were less close to vertical in low hydraulic conductivity layers compared to those with high hydraulic conductivity. Moreover, [64][65][66] also associated the bending of the thermal contours with the refraction of the heat flow. They demonstrated that the variation of thermal conductivity within the aquifer materials produced the refraction.…”
Section: Discussionmentioning
confidence: 99%
“…The heat flux in the hydrothermally active area is easily disturbed. How to eliminate the influence of groundwater flow on terrestrial heat flow estimation is an important topic in geothermic research (Mansure and Reiter, 1979;Wang et al, 2021). Hu and Xiong (1994) achieved good results in heat flow correction in the southeastern coastal areas of China.…”
Section: Introductionmentioning
confidence: 99%